1998
DOI: 10.1021/jp982368c
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization of a Capped Azobenzene in Solution Probed by Ultrafast Time-Resolved Electronic Absorption Spectroscopy

Abstract: Ultrafast time-resolved electronic absorption spectroscopy has been used to study the photochemistry of trans-azobenzene and trans-1, a derivative in which azobenzene is capped by an azacrown ether, on UV excitation to the S2(ππ*) state. Excitation of trans-1 results in transient absorption which decays with a dominant component of lifetime ca. 2.6 ps and in bleaching of the ground-state UV absorption band which recovers on a similar time scale. In contrast, excitation of trans-azobenzene results in transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
88
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 20 publications
13
88
0
Order By: Relevance
“…The inversion mechanism is suggested to proceed via a linear transition state in which the N=N double bond remains intact, whereas the rotation mechanism is proposed to occur via a twisted transition state in which the N=N π-bond is broken. Upon photo-excitation of the trans form, an electron is excited from its ground-state (S 0 ) orbital to its first singlet excited state (S 1 ) or second singlet excited state (S 2 ) in which the electron retains its spin under an n-π* excitation condition or a π-π* excitation condition, respectively [1,2]. Azo groups are reported to photo-isomerize via two distinct mechanisms: the π-π* transition with an out-of-plane rotation mechanism in which the nitrogen-nitrogen π bond is ruptured heterolytically and a dipolar transition state is involved (Scheme 1), or the n-π* electronic transition with an inversion of one sp 2 hybridized nitrogen atom through an sp hybridized linear transition state in which the double bond is retained (Scheme 2) [2][3][4][5][6].…”
Section: Photo-isomerization Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inversion mechanism is suggested to proceed via a linear transition state in which the N=N double bond remains intact, whereas the rotation mechanism is proposed to occur via a twisted transition state in which the N=N π-bond is broken. Upon photo-excitation of the trans form, an electron is excited from its ground-state (S 0 ) orbital to its first singlet excited state (S 1 ) or second singlet excited state (S 2 ) in which the electron retains its spin under an n-π* excitation condition or a π-π* excitation condition, respectively [1,2]. Azo groups are reported to photo-isomerize via two distinct mechanisms: the π-π* transition with an out-of-plane rotation mechanism in which the nitrogen-nitrogen π bond is ruptured heterolytically and a dipolar transition state is involved (Scheme 1), or the n-π* electronic transition with an inversion of one sp 2 hybridized nitrogen atom through an sp hybridized linear transition state in which the double bond is retained (Scheme 2) [2][3][4][5][6].…”
Section: Photo-isomerization Mechanismsmentioning
confidence: 99%
“…Azobenzenes are common organic dyes that have been extensively studied both experimentally and theoretically owing to their potential applications in material science, medicinal chemistry, molecular switches and other devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. They are photo-reactive molecules that undergo reversible photo-isomerization from the more stable trans-isomer to the less stable cis-isomer.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] The corresponding reaction of cis-AB has been found to be even faster. 15,16 Most workers assumed the abovementioned semi-linear ''inversion'' pathway.…”
Section: Introductionmentioning
confidence: 99%
“…1 has previously been studied with femtosecond time resolution only after excitation to the S 2 state at l ¼ 303 nm, 13 while 2 has not been investigated at all to our knowledge. The molecules were excited to the S 1 state at l ¼ 475 nm and the ensuing dynamics were monitored by femtosecond fluorescence up-conversion spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the S 1 species (367-500 nm, ¾2.4 ps) observed on -Ł excitation of a rotationally blocked TAB derivative (capped TAB) differs both in transient absorption and decay kinetics from the S 1 species (370-450 nm, ¾1.0 ps) observed on -Ł excitation of TAB. 37 It, however, resembles the directly excited S 1 state of TAB (360-620 nm, ¾2.5 ps). 36,37 This indicates that the rotational pathway that lowers the isomerization yield is certainly involved in either the formation or decay of the transient S 1 species and it is possible that S 3 relaxes to S 1 (CNNC ¾100°) along the rotational pathway.…”
Section: Discussionmentioning
confidence: 94%